1996
DOI: 10.1099/0022-1317-77-3-485
|View full text |Cite
|
Sign up to set email alerts
|

The effect of UV-B irradiation on secondary epidermal infection of mice with herpes simplex virus type 1

Abstract: Previous studies have indicated that suberythemal ultraviolet B (UV-B) irradiation of C3H mice before primary infection with herpes simplex virus (HSV) type 1 does not result in increased morbidity or mortality, but a suppressed delayed type hypersensitivity (DH) to the virus can be demonstrated. Any effect of UV radiation on pathogenesis during secondary epidermal HSV infection has not been previously examined. Mice were immunized by subcutaneous injection of inactivated HSV and, 5 days later, one group was U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…A plaque‐purified strain of HSV‐1, isolated from a clinical case and passaged four times in Vero cells at a multiplicity of infection of 0.2, was used throughout [9]. The virus was cultured and titrated as plaque forming units (PFU) on monolayers of Vero cells as previously described [10]. Inactivated HSV was prepared by UV irradiating a virus stock with 12 000 J m −2 UV‐B.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A plaque‐purified strain of HSV‐1, isolated from a clinical case and passaged four times in Vero cells at a multiplicity of infection of 0.2, was used throughout [9]. The virus was cultured and titrated as plaque forming units (PFU) on monolayers of Vero cells as previously described [10]. Inactivated HSV was prepared by UV irradiating a virus stock with 12 000 J m −2 UV‐B.…”
Section: Methodsmentioning
confidence: 99%
“…The size of the lesions that formed on the backs of the mice was then measured with a ruler in two dimensions, each day for the next 10 days. This procedure has previously been shown to mimic a natural epidermal HSV infection and result in the formation of moderate vesicular lesions on the infected skin [10].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, numerous experimental models have shown that UVR suppresses immune responses against bacterial, viral, and fungal infections (Chapman et al, 1995). For example, mice that were immunized with the herpes simplex virus developed severe ulcerated lesions upon cutaneous herpes virus inoculation during which they were exposed to UVR before inoculation (El-Ghorr and Norval, 1996).…”
Section: Uvr-induced Immunosuppression and Microbial Infectionsmentioning
confidence: 99%
“…In addition to locally compromising the host's defense against skin tumors, UVB-induced systemic immune suppression may influence the development and course of infectious disease. Although the evidence that this type of immune suppression occurs in humans is less compelling and still incomplete, studies with rodents have clearly demonstrated that exposure to UVB suppresses the resistance against both systemic and non-skin-associated local infections [3][4][5][6][7]. However, the mechanism by which UVB impairs the immunity to infectious disease is not known.…”
Section: Introductionmentioning
confidence: 99%